Fast and Green – CO2 Based Extraction, Isolation, and Quantification of Phenolic Styrax Constituents - Scheuba, Johanna; Wronski, Valerie-Katharina; Rollinger, Judith M.; Grienke, Ulrike (Planta Medica, 2017)
In this study the first supercritical fluid based protocol for the extraction, analysis, and isolation of six polar compounds, i.e., o-vanillin (1), styracin (2), vanillin (3), trans-cinnamic acid (4), vanillic acid (5), and shikimic acid (6), was developed. First, eight styrax resin products (R1–R8) obtained from various Liquidambar tree species, which are known to contain compounds 2–6, were extracted with a 1 : 1 mixture of supercritical CO2 and EtOH. Within 4 minutes, the compounds were successfully baseline separated on an Acquity UPC2 BEH 2-EP (3.0 × 100 mm, 1.7 µm) column using a mobile phase of supercritical CO2 and MeOH with 0.1 % phosphoric acid. The compounds were quantified and the method was validated according to current ICH guidelines. Scaling up to preparative supercritical fluid chromatography using a Viridis BEH 2-EP (10 × 250 mm, 5 µm) column allowed for a fast separation and isolation of the selected constituents 2 and 4 from R6 within 7 minutes. This supercritical fluid protocol is easily adaptable to compounds of similar polarity. The increase in speed and its environmental friendliness underline its superiority over conventional set-ups.
Keywords: Liquidambar orientalis; Hamamelidaceae; supercritical fluid extraction; supercritical fluid chromatography; ultra-performance convergence chromatography; styrax